Biogas bioconversion into poly(3-hydroxybutyrate) by a mixed microbial culture in a novel Taylor flow bioreactor. (1st August 2022) - Cattaneo, Carlos R.; Rodríguez, Yadira; Rene, Eldon R.; García-Depraect, Octavio; Muñoz, Raúl
Graphical abstract: Abstract: Biogas-based biopolymer production represents an alternative biogas valorization route with potential to cut down plastic pollution and greenhouse gas emissions. This study investigated for the first time the continuous bioconversion of methane, contained in biogas, into poly(3-hydroxybutyrate) (PHB) by a mixed methanotrophic culture using an innovative high mass-transfer Taylor flow bioreactor. Following a hydrodynamic flow regime mapping, the influence of the gas residence time and the internal gas recirculation on CH4 abatement was assessed under non nutrient limiting conditions. Under optimal operational conditions (gas residence time of 60 min and internal gas recycling ratio of 17), the bioreactor was able to support a CH4 removal efficiency of 63.3%, a robust CH4 elimination capacity (17.2 g-CH4 m -3 h -1 ) and a stable biomass concentration (1.0 g L -1 ). The simultaneous CH4 abatement and PHB synthesis was investigated under 24-h:24-h nitrogen feast/famine continuous operation. The cyclic nitrogen starvation and the Taylor flow imposed in the bioreactor resulted in a relatively constant biomass concentration of 0.6 g L -1 with PHB contents ranging from 11 to 32% w w -1 (on a dry weight basis), entailing an average PHB productivity of 5.9 g-PHB m -3 d -1 with an associated PHB yield of 19.8 mg-PHB g-CH4 -1 . Finally, the molecular analysis of the microbial population structure indicated that type II methanotrophs outcompeted non-PHB accumulating type I methanotrophs, with a heterotrophic-methanotrophic consortium enriched in Methylocystis, Hyphomicrobium, Rubinisphaeraceae SH PL14 and Pseudonocardia .